All Days 2012
DOI: 10.2118/155199-ms
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of MIC in Carbon Steel Water Injection Pipelines

Abstract: The present study compares corrosion mass loss and pit depth measurements on carbon steel corrosion coupons exposed under similar operating parameters, but with different biological consortia. One set of data were obtained from standard flush disc corrosion coupons used to monitor corrosion rates in a water injection pipeline on the North Sea continental shelf. The coupons were exposed on average for 6 months over 6 years operational time. These data are compared with published corrosion data of coupons expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…However, the limited amount of corrosion observed (up to 0.06 mm/year) suggests a passivation phenomenon rather than active biocorrosion. A more environmental-oriented study from Comanescu et al found that water injection pipelines for secondary oil recovery with average temperatures 50–60°C presented deeper pits and higher bacterial counts than those with average temperatures between 60 and 120°C (Comanescu et al, 2012 ). Although interesting, such study is probably less relevant for production pipelines, since a low amount of oxygen is present in water injection pipelines, along with different pools of electron donors and acceptors, correlated with the origin of the waters (groundwater, seawater, or river/lakes).…”
Section: Discussionmentioning
confidence: 99%
“…However, the limited amount of corrosion observed (up to 0.06 mm/year) suggests a passivation phenomenon rather than active biocorrosion. A more environmental-oriented study from Comanescu et al found that water injection pipelines for secondary oil recovery with average temperatures 50–60°C presented deeper pits and higher bacterial counts than those with average temperatures between 60 and 120°C (Comanescu et al, 2012 ). Although interesting, such study is probably less relevant for production pipelines, since a low amount of oxygen is present in water injection pipelines, along with different pools of electron donors and acceptors, correlated with the origin of the waters (groundwater, seawater, or river/lakes).…”
Section: Discussionmentioning
confidence: 99%
“…The severe channelling corrosion sometimes observed in offshore water injection pipelines is assumed to be associated with microbiologically influenced corrosion and much attention has been given to this possibility in the practices adopted by industry (Comanescu et al, 2012;Comanescu et al, 2016;Heidersbach and van Roodselaar, 2012). The potential influence of under-deposit corrosion has been given much less attention even though there is circumstantial evidence for it from field observations (Heidersbach and van Roodselaar, 2012).…”
Section: Industrial Significancementioning
confidence: 99%
“…Microbiologically influenced corrosion (MIC) such as sulfate reducing bacteria (SRB) in biofilm consortia has signalled the role of this particular bacterium in the process of corrosion in pipelines and seawater injection systems (AlAbbas 2013; Almahamedh et al 2011;Comanescu et al 2012;Maxwell & Campbell 2006). It is well-known that MIC can oxidize a wide variety of chemicals and use them as nutrient sources and enhance their proliferation.…”
Section: Introductionmentioning
confidence: 99%